PENGARUH PERSONAL REFERENCE, THOUGHT AND FEELING TERHADAP KESEHATAN REPRODUKSI SANTRI PUTRI PONDOK PESANTREN X - Amanda Nazira; Shrimarti Rukmini Devy (Universitas Airlangga, 2017)
There are still many reproductive health problems in Indonesia which require attention from all parties. The reproductive health problems are caused by the lack of knowledge, comprehension and low responsibility among adolescents along with the limited access to the information of reproductive organs and functions. Therefore, personal hygiene in term of proper treatment for the reproductive organs is needed to decrease the problem of infectious diseases on reproductive organs. This study was conducted to examine the effect of personal reference, thought and feeling with behavioral treatments of reproductive organs among female students at X Islamic Boarding School, Jombang. This study employed observational design since the data collection was obtained without treatment of the sample as well as using cross sectional study design to the 45 respondents. The respondents were drawn from a population based on the simple random sampling method. The results of logistic regression test indicated that the factors which infl uence behavioral treatments on reproductive organs among female students are the respondents knowledge (p = 0,029; OR = 0,165), attitude (p = 0,009; OR = 0,113) and personal reference (p = 0,049; OR = 0,199). The personal reference was the most infl uent factor among female students in conducting behavioral treatment of their reproductive organs at X Islamic Boarding School, Jombang. Keywords: female students, Islamic boarding school, personal reference, reproductive health, thought and feeling.